Mesothelial cell inclusions mimickingadenocarcinoma in cervical lymph nodes in association with chylous effusion - Goyal, Manu; Kodandapani, Suseela; Sharanabasappa, S Nirni; Palanki, Satya Dattatreya (Indian Journal of Medical and Paediatric Oncology, 2010)
Mesothelial cell inclusions in lymph nodes are of rare occurrence and can be mistaken as metastatic adenocarcinomas, mesothelioma or sinus histiocytosis. These are usually found in mediastinal and abdominal lymph nodes and are associated with effusions. We report a case of benign mesothelial cell inclusions in cervical lymph nodes, which was associated with chylous effusion, and immunohistochemistry revealed unusual weak cytoplasmic epithelial membrane antigen positivity in the cells.
Keywords: Adenocarcinoma; chylous effusion; epithelial membrane antigen; mesothelial cell inclusions